Uzbekistan : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
Uzbekistan inherited the Soviet system for the procurement of goods, works and services for State needs. This system was suitable for a command economy but lacks the essential elements of competitiveness, transparency and accountability, which are the hallmarks of a market-based approach to government contracting. This Country Procurement Assessment Report (CPAR) comes at a time when a number of factors are creating an increased need for public procurement reform. Primary among these is that Uzbekistan has concluded a Partnership and Cooperation Agreement (PCA) with the European Union which commits the Government to develop conditions for open and competitive award of procurement contracts. Also, the country's application for membership to the World Trade Organization (WTO) may lead to accession to the WTO Agreement on Government Procurement (GPA), thereby creating an obligation on Uzbekistan to align its procurement legislation with the GPA. The report, examines all areas of public procurement operations, including, legislative framework, performance of regulatory functions, capacity of public sector institutions and the effects of corruption on procurement. It also recommends the Government to prepare a new draft Law on Public Procurement based on the January 2000 draft Law on Government Procurement.